Determinants of Private University Choice in Banten: The Role of Institutional Reputation and Location - Sentosa, Bambang Mardi; Pradesti, Ajeng; Khusaini, Khusaini (Jurnal Pendidikan Progresif, 2025)
Determinants of Private University Choice in Banten: The Role of Institutional Reputation and Location. Objectives: Accurately selecting a university can significantly impact one’s future, including career prospects, job market oportunities, and overall well-being. Previous findings have been debated among researchers regarding the relationship between gender, a university's reputation, location, and tuition fees with university choice. However, studies in the context of private universities in Banten, such as Syekh Yusuf Islamic University (UNIS), are limited and require further research. This study aims to examine the influence of gender, reputation, location, and tuition fees on students' choice of UNIS. Methods: This study utilized a quantitative approach and a binary logistic regression model. The sample size was 937 participants. A validated online Google Forms questionnaire was distributed through WhatsApp groups to collect the data. Findings: The results of the binary logit analysis showed that university reputation and location had a significant influence on the selection of UNIS. Reputation increased students' chances of choosing UNIS, as did a strategic campus location. Conversely, neither gender nor tuition fees were found to influence students' decisions to choose UNIS. These findings confirmed that campus reputation and accessibility are the primary factors influencing students’ choice of UNIS.  Conclusion: The findings of this study provide empirical evidence that UNIS needs to prioritize strengthening its academic reputation as a key factor in attracting prospective students. To address this, improving faculty quality, pursuing program accreditation, and collaborating with industry are strategic steps to strengthen the institution's image. Additionally, its strategic location must be continually optimized through enhanced accessibility and transportation infrastructure, which further supports student recruitment. While tuition fees have not proven to be a significant barrier, maintaining a transparent fee policy and offering scholarships remains necessary to stay competitive. In summary, focusing on both reputation and accessibility will strengthen UNIS's position as a leading private university in Banten. Keywords: gender, location, reputation, tuition fees, university choice.